0060 Sleep disparities by race/ethnicity during pregnancy: an Environmental influences on Child Health Outcomes (ECHO) study. (25th May 2022) - Lucchini, Maristella; O'Brien, Louise; Kahn, Linda; Brennan, Patricia; Baron, Kelly; Knapp, Emily; Lugo, Claudia; Shuffrey, Lauren; Dunietz, Galit; Zhu, Yeyi; Alcantara, Carmela; Fifer, William; et al.
Abstract: Introduction: Poor sleep during pregnancy is common and associated with increased risk of adverse perinatal outcomes. Racial/ethnic minoritized groups in the United States experience worse sleep than non-Hispanic Whites (nHW), likely due to downstream effects of systemic and structural discrimination. Nonetheless, the extent of sleep disparities in the perinatal period remains understudied. In this analysis we estimated the prevalence of subjective measures of sleep in a multi-racial/ethnic pregnant population from the Environmental influences on Child Health Outcomes (ECHO) program. Methods: Participants self-reported their race and ethnicity and were grouped into four categories: 1)nHW, 2)non-Hispanic Black/African American (nHB/AA), 3)Hispanic, 4)non-Hispanic Asian (nHA). Our analysis examined trimester-specific nocturnal sleep duration, sleep quality, and sleep disturbances (derived from the Pittsburgh Sleep Quality Index and the ECHO maternal sleep health questionnaire) by race/ethnicity. A total of 1119, 2409 and 1284 participants in the first (T1), second (T2) and third trimesters (T3) reported on sleep duration. 1107, 1742 and 783 participants in T1, T2 and T3 reported on sleep quality. 1112, 1758, and 787 participants in T1, T2 and T3 reported on sleep disturbances Linear or multinomial regression were used to estimate associations between race/ethnicity and each sleep domain by trimester, controlling for body mass index (BMI) and age. We repeated analyses within education strata (high school degree, GED/equivalent; some college and above) Results: nHB/AA participants reported shorter sleep duration (T2: β=-0.55 [-0.80, -0.31]: T3: β=-0.65 [-0.99, -0.31]), and more sleep disturbances (T2:β=1.92 [1.09, 2.75]; T3:β=1.41 [0.09, 2.74]) compared to nHW. Hispanic participants reported longer duration compared to nHW (T1: β=0.22 [0.00004, 0.44];T2: β=0.61 [0.47, 0.76];T3: β=0.46 [0.22, 0.70]), better sleep quality (Compare to Very good quality OR for Fairly good T1: OR=0.48 [0.32, 0.73], T2: OR=0.36 [0.26, 0.48], T3: OR=0.31 [0.18, 0.52]; Fairly bad T1:OR=0.27 [0.16, 0.44], T2:OR=0.46 [0.31, 0.67], T3: OR=0.31[0.17, 0.55]), and fewer sleep disturbances (T2 β=-0.5 [-1.0, -0.12]; T3 β=-1.21 [-2.07, -0.35]). Differences persisted within the subsample of high SES women. Conclusion: These findings highlight racial/ethnic disparities across multiple domains of sleep health during pregnancy. Given the stark racial/ethnic disparities in perinatal outcomes and their associations with sleep health, further research is warranted to investigate the determinants of these disparities, such as downstream effects of systemic and structural discrimination Support (If Any):